IMPLEMENTATION OF DMAIC METHODS TO REDUCE SCRAP IN PLASTIC INJECTION MOLDING AREA AT PT.ABC INDONESIA - Denartha Randhika; Ir. Andira Taslim M.T. (JIE Scientific Journal on Research and Application of Industrial System, 2024)
ABSTRACT PT.ABC Indonesia has a project to reduce high number of scraps in Primary Production area. Plastic Injection Molding area contributes over 50% from total scrap in Primary Production area and resulted scrap value that total Rp. 378.803.000 in first quarter of 2023. These scraps happen because of the changeover process procedure. This research use Lean Six Sigma approach through DMAIC Methodology. Several improvements are implemented new procedure for color change and tool change without purging process and slide the hopper when Daily Schedule Adherence achieve 95%. The improvement resulted 57% reduction of scrap in Plastic Injection Molding. In detail, color change and tool change procedure reduce 62% scrap, While the slide hopper process was reduce wrong color scrap by 16%. By this research, the company already saving the cost Rp. 49.237.000 and predicted will save up to Rp. 434.660.000 by the end of year 2023. Keywords: DMAIC, Lean, Six Sigma, Plastic Injection Molding, Purging, Scrap, Wrong Color. ABSTRAK PT.ABC Indonesia memiliki projek untuk mengurangi jumlah skrap di area produksi primer. Area Plastik Injeksi Moulding menyumbang lebih dari 50% dari jumlah skrap pada area produksi primer dan menghasilkan skrap dengan nilai sebesar Rp. 378.803.000 pada kuartal pertama di 2023. Skrap terjadi karena prosedur proses changeover. Riset ini mengaplikasikan pendekatan Lean Six Sigma melalui metode DMAIC. Adapun penyempurnaan yang dilakukan adalah mengimplementasikan prosedur baru untuk pergantian warna dan juga pergantian alat tanpa perlu proses purging, menggeser hopper saat Keterpenuhan Jadwal Harian sudah mencapai angka 95%. Penyempurnaan ini menghasilkan berkurangnya skrap sebesar 57% pada area Plastik Injeksi Moulding. Secara rinci, prosedur penggantian warna dan penggantian alat mengurangi skrap sebesar 62%, dan proses penggeseran hopper mengurangi skrap wrong color sebesar 16%. Dari riset ini, perusahaan sudah melakukan penghematan sebesar Rp. 49.237.000 dan diperkirakan akan menghemat sampai dengan Rp. 434.660.000 di akhir tahun 2023. Keywords: DMAIC, Lean, Six Sigma, Plastik Injeksi Moulding, Purging, Skrap, Wrong Color.